Pope, Church and City
1 online resource.
Keywords: This illustrated volume is an articulate series of essays by distinguished authors on themes which are central to the work of Brenda Bolton as a scholar and teacher: Innocent III, the city of Rome, the late medieval Church and the urban context of the Italian peninsula in the twelfth to fourteenth centuries. The essays combine groundbreaking new analyses with careful reading of the sources to demonstrate the vibrancy of the study of the ecclesiastical and social history of the Mediterranean in the late Middle Ages.